Exploration of Use-Case-Dependent Modeling Approach for Distributed DC-Grids - Lavery, Melanie; Schwanninger, Raffael; März, Martin (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
In this paper, the previously described Use-Case-Dependent Modeling Approach is evaluated and its usefulness for grid simulation is explored. One of the main merits of the approach is its application in automated system analysis. Previous results also suggest a reduced usage of computing resources. This however has not yet been systematically tested and properly verified. Therefore, to inspect the validity of this approach, the methodology is explained and simulation results are compared to measurements of the modeled DC system. It is shown that the grid models adequately represent the system's behavior and the simulation results can therefore be used for system analysis. Discrepancies can be explained by an insufficient modeling of the measured system's damping elements. These differences are however small enough to be mitigated by usually applied error margins, especially for system stability analysis. Although more work is required for full verification, the validity and versatility of the approach is demonstrate